2010
DOI: 10.3109/17482968.2010.536985
|View full text |Cite
|
Sign up to set email alerts
|

The thermolabile variant of 5,10-methylenetetrahydrofolate reductase is a possible risk factor for amyotrophic lateral sclerosis

Abstract: Hyperhomocysteinemia is a risk factor for neurodegeneration, and binding of copper by homocysteine is a putative underlying mechanism. As mutations of the copper-dependent superoxide dismutase are observed in familial ALS, we tested whether genetic variants with influence on homocysteine metabolism are associated with ALS. We compared the frequency of seven variants of genes involved in homocysteine metabolism in 162 patients with sporadic ALS and 162 controls who did not significantly differ in age (t = 1.27,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Similarly, the allele frequency analysis showed that the T allele confers risk for disease susceptibility (OR = 1.54; 95% CI = 1.05-2.29) (p = 0.03) (Table 2). The same results were found in studies by [72] and [73].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the allele frequency analysis showed that the T allele confers risk for disease susceptibility (OR = 1.54; 95% CI = 1.05-2.29) (p = 0.03) (Table 2). The same results were found in studies by [72] and [73].…”
Section: Discussionsupporting
confidence: 89%
“…However, conflicting data should also be mentioned. Thus, while some authors found a link between MTHFR C677T polymorphisms as risk factors for ALS (Kühnlein et al, 2011 ; Sazci et al, 2012 ) others (Ricci et al, 2012 ) did not detect a direct association between the two.…”
Section: Discussionmentioning
confidence: 95%
“…Inherited deficiency of the enzyme methylenetetrahydrofolate reductase (MTHFR), transforming HCY into methionine through remethylation, is associated with severe muscular hypotonia (Huemer et al, 2015 ). There is conflicting evidence about the role of the frequent MTHFR C677T polymorphisms as risk factors for ALS (Kühnlein et al, 2011 ; Ricci et al, 2012 ; Sazci et al, 2012 ). The variant MTHFR C677T, known to be associated with increased levels of HCY (Kang et al, 1988 ; Li et al, 2003 ) is more frequent among ALS patients (Kühnlein et al, 2011 ), however an Italian population study found no association (Ricci et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs in the gene encoding the ESR1 co‐activator PPARGC1A are associated with age of ALS onset and survival in males specifically . Moreover, genetic variations in MTHFR – which encodes an important enzyme in the folate cycle – and in the promoter region of the growth factor VEGFA have been associated with ALS in women. These notions imply that the presumed hormonal neuroprotective advantage of women could be counteracted by genetic variations in, for example, the folate cycle and/or VEGF signaling.…”
Section: Discussionmentioning
confidence: 99%